A case study on students’ perception on factors of absenteeism that may affects AM228 students performance at UiTM Malacca City Campus / Faez Ismael Shamsudin and Saidatul Syamin Said - Shamsudin, Faez Ismael; Said, Saidatul Syamin (Faculty of Administrative Science and Policy Studies, 2012)
The purpose of this research is to identify the students’ perception on factors of absenteeism that may affect AM228 students’ performance at UiTM Malacca City Campus. The factors of absenteeism include the class environment, peers influence, lecturers’ attitude and students’ attitude. The objectives of this study were to identify the students’ perception on the above mentioned factors (class environment, peers influence, lecturers’ attitude and students’ attitude) that may affect on AM228 students’ performance in UiTM Malacca City Campus. The study adopted the cross sectional study and used a set of questionnaire as the operational framework for data gathering. Data were collected by self administered questionnaires with one hundred and thirty-one students from AM228 students in semester 2 until semester 6. The correlation analysis of the data showed that class environment (r= .296, p= .000), peers influence (r= .277, p= .000) and lecturers’ attitude (r= .321, p= .000) were interrelated with the students’ performance. Meanwhile, the students’ attitude (r= -.034, p= .351) did not influences the students’ performance in their study. For conclusion, the study has achieved the objectives which are to identify the students’ perception on the factors of absenteeism that may affect AM 228 students’ performance at UiTM Malacca City Campus. It was found that students’ performance may be affected by factors such as class environment, peers pressure and lecturers’ attitude. This is because those factors believed to have a significant relationship towards students’ performance. On the other hand, it was found that students’ attitude did not have a significant effect towards the students’ performance.